How is COVID-19 perceived by medical students? A survey in Aceh province, Indonesia - Rina S. Oktari (AOSIS, 2021)
The coronavirus disease 2019 (COVID-19) has burdened the health system and medical education programmes both locally and globally, requiring medical students to continue their education whilst engaging in prevention programmes to support primary health services. This study aims to describe medical students’ knowledge, attitudes in the prevention of COVID-19, and to determine the relationship between the knowledge of COVID-19 preventive behaviour and attitudes towards it. This study used an analytical cross-sectional observational design with a sample of 290 students. Data were collected through a self-assessment method using a validated questionnaire. Analysis of the frequency distribution test for knowledge found that 54.1% of the respondents and 99.0% of the students had a good understanding of the mode of transmission of COVID-19. The majority of medical students (73.1%) also had a good attitude towards COVID-19 and around 84.3% of the students considered that good ethics is needed when coughing or sneezing during this pandemic. As many as 46.6% of the respondents had good preventive behaviour against COVID-19 and always imposed restrictions on using public transportation during a pandemic. The Spearman’s correlation test shows a weak but meaningful relationship between knowledge (r = 0.214, p = 0.000) and COVID-19 preventive behaviour, and a significant relationship between attitudes (r = 0.477, p = 0.000) towards COVID-19 preventive behaviour. This study concludes that medical students have good knowledge, preventive behaviour and an understanding of infection risk. An enhanced knowledge and awareness will increase preventive behaviours that will provide support in controlling the disease.